METOCEAN STUDY FOR SUBMARINE PIPELINE MAINTENANCE - Arissaputra N, Deni
Submerged pipe must be designed to be able to withstand loads through its operational life. Pipe surroundings could give loads. Hydrodynamic load is a load caused by water flow around the pipe. Loads is harmfull to pipe system, that could lead to system failure. Metocean study is one of pipe maintenance procedure. The aim in this study is to investigate the characteristics of the meteorology and oceanography phenomena, their correlation, and the impact to water current. Observation was done for 8 days in Mahakam River’s child, using hydro-acoustic device Doppler type, Acoustic Doppler Current Profiler (ADCP). Harmonic analysis was done to know the tide type, it is mixed tend semi-diurnal. Spectral analysis was done to decompose the current data. Using spectral analysis, power of the forming frequency can be known. The current is dominated by the river flow, but tidal wave gives significant impact to the water current. Extreme current estimation was done by fitting the residual stocastic current into generalized extreme value (GEV) distribution. It is obtained by eliminating the river flow and tide current from the current data. Considering the length of observation, estimation was done to get the 30-days extreme current, which is 11,390 cm/s. The value of parameters of current velocity in GEV distribution is: ? =0,051, ? =4,141, ? =6,612. Using the current conditions, assessment of pipe hydrodynamic loads was done.